Det jødiske folk og folkelighedsbegrebet i 1814-krøniken - Pedersen, Kim Arne (Grundtvig-Studier, 2015)
Det jødiske folk og folkelighedsbegrebet i 1814-krøniken Kim Arne Pedersen The Jewish people and the Concept of “folkelighed” in the World Chronicle of 1814 The article describes Grundtvig’s concept of “folkelighed” in The World Chronicle from 1814 and its relationship with Grundtvig’s political opinions, theology, and history. The study confirms discoveries of previous research that Grundtvig was inspired by J.G. Herder’s ideas about national identity and Fichte’s idea of “normal people,” but it argues that Grundtvig opposed a number of contemporary discussions about Judaism. Grundtvig was quite familiar with the Old Testament research of his day which followed the general negative attitudes toward Jews in society. In the 1814 Chronicle, he offers a clear alternative to these negative views through his popular concept, which surprisingly turns out to be an essential component of his later political thought. Therefore, the article demonstrates a crucial aspect in Grundtvig’s thinking as a young man, which previous research has failed to highlight even though it is in many ways a prerequisite for understanding how his political ideals and worldview developed from the 1830s to find consistent expression in his writing.